(untitled) (INTERNATIONAL CONFERENCE ON MEDICINE, SCIENCE, AND EDUCATION, 2024)
This study examines the reflection of clothing items in English and Uzbek through corpus linguistics. By analyzing linguistic patterns and cultural significances associated with clothing, we uncover the interplay between language, identity, and tradition. Findings reveal both shared themes and distinct differences in how clothing is conceptualized, reflecting broader societal values.